PARENTING FROM THE PERSPECTIVE OF CHILDREN AND PARENTS IN CIBUNTU VILLAGE - Adriany, Dita; Putri, Dita Radika; Khoirunnisa, Dhiya; Fathimah, Mitha; Jefry, Mohammad; Fitriah, Nabilah; Supriatna, Mamat (Study Program Guidance and Counseling, Univesitas Pendidik, 2025)
Parental care is important for children. Parenting is also an effort to understand the needs and desires of children, as well as parents must be able to see the development and growth of children, so that they can become superior seeds for the next generation. However, there are still many who do not understand what good parenting is like, so with the field trip to Cibuntu village, it can explore information on the extent to which Cibuntu Village parents understand parenting patterns for their children. Nowadays, there will definitely be many challenges that parents will face, especially in the era of digitalization. Therefore, the resource persons from Cibuntu Village were measured for their knowledge and the extent to which they understand parenting.